ANALISIS KESALAHAN PENULISAN KATA DENGAN MENGGUNAKAN METODE IMLA’ AL-MASMÛ DI KALANGAN MAHASISWA PBA UINSU - Siti Rahma; Azizah Sabrina Gajah; Ernida Hasibuan; Sahkholid Nasution; L'Niana Aulia Zuhri Dalimunthe (Yayasan Haiah Nusratul Islam, 2023)
This research was motivated by the problem that was found that there were still many students lacking training in writing Arabic, especially in imla'. Therefore, research was carried out on the analysis of word writing errors using the imla' al-masmu' method which aims to describe the forms of errors and the causes of errors in writing Arabic at the student level. The type of this research is a descriptive qualitative approach with analysis applying the Rusydi Ahmad Tha'imah method, divided into three stages, namely three steps, namely error recognition (Ta'rif Al-Khatha'), exposure and error data (Tausif Al-Khata') along with the interpretation and explanation of errors (Tafsir Al-Khata') in the documentation results of Arabic language education students 1 Stambuk 2021 UINSU, totaling 33 documentations. This research collects data by applying methods, namely documentation, observation and interviews. The results of this research show that imla' errors were made 6 times. These types of errors include errors in identifying the sounds of Arabic letters, errors in connecting letters, errors in the use of tanwin, errors in the use of ta' marbutha, errors in the use of mad, errors in writing the hijaiyah form. The factors that cause errors in writing Arabic are the reader's lack of clarity in pronouncing the letters, dictating too quickly and students not really understanding the rules of imla' well